Idea hegemonii kulturowej Polski i Polaków w prozie podróżniczej Aleksandra Sapiehy - Karpińska, Monika (Wydawnictwo Uniwersytetu Rzeszowskiego, 2017)
The aim of the article is to present the idea of Slav present in the prose of Aleksander Sapieha. Traveler in his relation reveals the cultural stratification of the Slavs, focusing not only on diverse religious influences, but also came from different areas of broad culture. Sapieha, noting those delamination, adheres to the idea of the superiority of the Poles among the Slavs, based mainly on the achievements of European civilization. The piece reflects on the idea of cultural hegemony, coming into conflict with affirmed in the eighteenth century, the vision of the Slavic tribal unity.
The idea of cultural hegemony Polish and Poles in the prose of travel Aleksander Sapieha
Keywords: Slavic; Aleksander Sapieha; cultural hegemony; prose of travel; Słowiańszczyzna; hegemonia kulturowa; proza podróżnicza